2018
DOI: 10.1172/jci122466
|View full text |Cite
|
Sign up to set email alerts
|

Fc-dependent functions are redundant to efficacy of anti-HIV antibody PGT121 in macaques

Abstract: Freidman test with Dunn's post hoc tests was applied. Nonpaired data were compared using 2-tailed Mann-Whitney U tests. For all statistical tests, P values of less than 0.05 were considered significant. Study approval. The Australian Commonwealth Scientific and Industrial Research Organization Animal Health Animal Ethics Committee approved all macaque studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
87
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(94 citation statements)
references
References 36 publications
6
87
1
Order By: Relevance
“…Instead, the data support a view that both ART and bNAbs act primarily by limiting viral replication and spread. The greater relative importance of neutralization over Fc function may be especially true in the case of highly potent bNAbs such as PGT121, which was able to protect monkeys from SHIV challenge despite abrogation of Fc receptor binding 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the data support a view that both ART and bNAbs act primarily by limiting viral replication and spread. The greater relative importance of neutralization over Fc function may be especially true in the case of highly potent bNAbs such as PGT121, which was able to protect monkeys from SHIV challenge despite abrogation of Fc receptor binding 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, Fc receptor functions of antibodies, such as ADCC, may play a crucial role in eliminating these cells (34,63,64). Several studies have demonstrated the importance of Fc receptor function of non-NAbs and bNAbs, although some controversy has recently been raised on the importance of the Fc-mediated function in one study of the mAb PGT121 (65). Recent results from a phase IIa clinical trial of coadministration of romidepsin with 3BNC117 demonstrated no obvious impact on the reduction of viral reservoir or the delay in viral rebound (12), thus support- seronegative and HIV-seropositive donors were obtained by Ficoll gradient from buffy coats.…”
Section: Discussionmentioning
confidence: 99%
“…This review highlights the potential role of FcγR-mediated Ab immune functions besides neutralization in protection against HIV. Although the role of the Fc-mediated function of Abs lacking broadly neutralizing activity for HIV protection is still a matter of debate (160,200), numerous independent studies now hint at their relevance for HIV inhibition. Above all, the specific Fc-mediated functions of non-NAbs are the only correlates of protection against infection observed in the RV144 vaccine trial conducted in Thailand (28,29,193,201).…”
Section: Discussionmentioning
confidence: 99%